Manilkara zapota L. extract topical ointment application to skin wounds in rats speeds up the healing process - Alsareii, Saeed Ali; Alzerwi, Nasser A. N.; Alasmari, Mansour Yousef; Alamri, Abdulrahman Manaa; Mahnashi, Mater H.; Shaikh, Ibrahim Ahmed; Savant, Chetan; Kulkarni, Preeti V.; Shettar, Arun K.; Hoskeri, Joy H.; Kumbar, Vijay (Frontiers in Pharmacology, 2023)
Poor circulation, unresolved inflammation, neuropathy, and infection make wound care difficult. Manilkara zapota (M. zapota) antibacterial and antioxidant properties may help speed up the healing process. The present investigation aimed to evaluate the wound healing activity of M. zapota bark ethanolic extract (MZE) by employing in-vitro migration scratch assay and in-vivo animal models. Wistar albino rats were used for the in-vivo wound healing models. No treatment was given to Group I; Group II received povidone-iodine (5% W/W); Group III received MZE (5 % W/W); and Group IV received MZE (10 % W/W). Linear incision models and excision wound models were used to induce injury. The ointments were applied immediately to the wounds after causing the injury. The percentage of wound contraction, the length of the epithelization period, and the wound's tensile strength were all calculated. The scratch assay assessed the test drug's potential for wound healing in-vitro. H2O2 and DPPH scavenging assays were used to measure antioxidant activity. A p <0.05 was used to define statistical significance. On days 4, 8, 12, 16, and 20, the wound contraction potential of animals treated with MZE ointment was significantly higher (p < 0.001) than that of the control group. On day 20, the proportion of wound contraction in MZE-treated animals was 99.88 %, compared to 83.86 % in untreated animals. The test group had a significantly (p < 0.01) faster time to full epithelization than the control group. In the incision model, the control group had considerably lower mechanical strength (p < 0.001) than animals treated with MZE. In addition, MZE caused a significant increase (p < 0.001) in total protein and hydroxyproline levels. In the scratch experiment, test drug-treated cells showed a higher rate of cell migration than untreated cells. Furthermore, animals treated with MZE showed increased levels of epithelial tissue, collagen proliferation, and keratinization. To summarize, the current study found that M. zapota improved wound healing activity both in vitro and in vivo, as evidenced by the study results. M. zapota extract has significant wound-healing potential and could be a viable source of wound-healing nutraceuticals.